School Burnout Inventory: Latent Profile and Item Response Theory Analyses in Undergraduate Samples - May, Ross W.; Rivera, Peter M.; Rogge, Ronald D.; Fincham, Frank D. (Frontiers in Psychology, 2020)
The current research reports both latent profile (person-oriented) and item response theory analyses of the School Burnout Inventory (SBI) in U.S. undergraduate samples. Study 1 (n = 1,007) comprises a latent profile analysis that identified four mutually exclusive subgroups based on patterns of school burnout responses. Covariate analyses of grade point average and negative affect suggested that school burnout profiles function similarly to variable-oriented approaches. Study 2 (n = 544) explored longitudinal patterns of school burnout among college students via use of a repeated measures latent profile analysis. Findings suggested that the profiles identified reflect a relatively stable school burnout trajectory over time. Covariate analysis of sleep quality and academic engagement demonstrated differences across profiles but the patterns were similar to variable-oriented statistical approaches. Study 3 (n = 2364) utilized an item response theory analysis of the SBI to identify a short, efficient measure. Item information curves and graded response model item discrimination parameters identified a 4-item SBI scale (SBI-4) that offered reasonably high levels of information for assessing school burnout in comparison to the original 9-item SBI. Implications and future research are identified.